ChemInform Abstract: 5‐Chloropyrazole‐4‐carboxaldehydes as Synthon in Heterocyclic Synthesis. Issue 21 (6th May 2016) - Gouda, Moustafa A.; Abu‐Hashem, Ameen A.; Saad, Hamada H.; Elattar, Khaled M.
Abstract: Review: 100 refs.